Digital Competence in Teacher Education Curricula - Ilka Nagel (Nordic Journal of Comparative and International Education, 2021)
This qualitative study aims to contribute to the discourse on teacher educators’ knowledge by examining the impact of digitalisation. To explore how digital competence is addressed in local curricula and what is expected of teacher educators (TEDs) in terms of preparing student teachers for epistemic changes, I thematically analysed the programme descriptions, course descriptions, and plans for school practicum from six Norwegian teacher education institutions. The findings show that TEDs are expected to focus on the (pedagogical) use of digital tools. However, they are also supposed to teach student teachers how to foster pupils’ digital skills and digital responsibility while addressing digitalisation’s influences on society and culture, subjects’ contents, and educational practices. The findings imply that TEDs need an understanding of digitalisation’s implications for epistemic practices to foster student teachers’ digital competence and transformative digital agency.